Growth and Development of Short Rotation Woody Crops for Rural and Urban Applications - Zalesny, Jr; Pilipović, Andrej (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Integrating biomass production of short rotation woody crops (SRWCs), with their use in environmental applications to produce income, sequester carbon, and clean the environment, provides an opportunity to enhance livelihoods and increase ecosystem services in rural and urban communities. This book consists of 20 papers from the special issue on the Growth and Development of SRWCs for Rural and Urban Applications highlighting four genera (Phalaris L., Populus L., Robinia L., Salix L.) from 13 countries. In addition to the development and management of a Salix cultivar database, rural and urban applications represented in the book included: a) forest buffers, b) forest health screening, c) phytoremediation, d) short rotation coppice, e) volume production, and f) wastewater reuse.